A Practical Synthesis of Near-Infrared Benzannulated Xanthenoid Dyes - Li, Jin; Wei, Ruwei; Zhang, Xiaodong; Luo, Xiao; Qian, Xuhong; Yang, Youjun (Synlett, 2023)
Near-infrared dyes are sought after for their potential in biomedical applications. Benzoxanthene dyes with a non-oxygen bridging atom are expected to exhibit longer absorption and emission wavelengths than their oxygen-containing counterparts, yet their synthesis remains unaddressed. Herein, we report the first syntheses of non-oxygen-bridged benzoxanthenes starting from a 7-bromo-2-aminonaphthalene derivative, and discuss their photophysical properties as well as their potential for in vivo imaging.
Keywords: fluorescence; near-infrared; benzoxanthene; stability; synthesis